Business Plan Clothing Business “The X Aksha” in Bali (Journal of Entrepreneurship, Management and Industry (JEMI), 2022)
This research aims to evaluate all aspects of the business viability of the clothing business "The X Aksha". With the increasingly rampant competition in Indonesia, especially in terms of dress. Here "The x Aksha" offers summer casual style-themed clothing designs with good quality and affordable prices. The purpose of establishing "The x Aksha" is to provide several models of clothing that are environmentally friendly and comfortable to use during this pandemic with attractive designs and affordable prices. From the results of calculations on the financial aspect for 5 years, the NPV is Rp. 1,198,996,338 and the IRR is 68%, where the payback period is 1 year 2 months, so from these results it can be concluded that this clothing business project is feasible to run.